One-Way Communication System using CNN for Interaction between Deaf and Blind People - Sulaksono, Juli; Ayu Dwi Giriantari , Ida; Sudarma, Made; Swarmardika , Ida Bagus Alit Swarmardika (Register: Jurnal Ilmiah Teknologi Sistem Informasi, 2025)
Communication is essential for everyone, including for individuals who are deaf and blind. People with disabilities must have equal rights to communicate, just like the general public. A one-way communication system between deaf and blind people is therefore necessary. The input to the system is in the form of spoken language, and the output is in the form of Braille. The input uses SIBI (Indonesian Sign Language System), which is recorded with a camera and then processed using a Convolutional Neural Network (CNN). The CNN is divided into three parts: the Training Process using a Tecnable machine, the SIBI DataSet model, and the Detection Process. The output of this process is text. The conversion of text into Braille is conducted using an image index. The resulting Braille can be read by blind users. System performance is analysed using a Confusion Matrix. The analysis results show an accuracy of 85%, a precision of 90%, and a recall of 82%.